A STUDY ON AWARENESS ABOUT HACKATHON AND ITS IMPACT ON INNOVATIVE STARTUPS IN TAMIL NADU - R. Ramachandran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Hackathons have become essential platforms for fostering innovation, entrepreneurship, and problem-solving among youth. This study explores the awareness of hackathons and their impact on innovative startup development in Tamil Nadu. Using a descriptive research design with 150 respondents comprising students, entrepreneurs, and professionals, the study applies ANOVA, Chi-square, and multiple regression analyses. Results show that hackathon participation significantly influences startup initiation and innovation levels. Mentorship, funding, and institutional support are the strongest predictors of post-hackathon startup success. Demographic factors such as age, gender, and education affect awareness levels and participation patterns. The findings emphasize that hackathons, when supported by structured mentorship and funding mechanisms, can transform creative ideas into viable businesses. Policy interventions from educational institutions and government agencies are suggested to strengthen the hackathon-driven entrepreneurial ecosystem.